Modes of cannabis use, frequency of use, and cannabis use problems: A latent profile analysis of modes of cannabis use - Dyar, Christina; Green, Elise; Rhew, Isaac C. (Addictive behaviors, 2025)
•Predominate edible use was associated with less cannabis use and fewer problems.•Predominate concentrate vaping was associated with more cannabis use problems.•Predominate concentrate vaping was associated with increases in frequency of cannabis use.•Using multiple modes of use each day was not associated with frequency or problems. While studies have linked different modes of cannabis use (CU) with CU problems and consequences, they have typically focused on unique effects of individual modes. Few studies have examined more complex patterns (e.g., using multiple modes). Studies that have typically combine modes and frequency of use, making it impossible to determine whether differences between patterns of use result from differing modes or differing frequencies of use. We used data from 338 sexual minority women and gender diverse individuals (18–25 years old) who used cannabis (populations at high risk for CU disorder) to identify groups based on their modes of CU and examine associations between mode-based groups on CU frequency and consequences. Four groups were identified: smoking [reference], vaping concentrates, edible use, and multiple modes of use. Those who predominately used edibles tended to engage in less frequent CU and reported fewer problems compared to those who predominately smoked cannabis. Individuals who predominately vaped concentrates experienced more problems and more frequent CU at follow-up compared to those who predominately smoked cannabis, controlling for CU problems and frequency at baseline. Using multiple modes per day was not associated with frequency or problems. Lower CU problems identified among those who predominately used edibles were attributed to their lower frequency CU. Findings also indicate that vaping concentrates may be associated with increasing cannabis frequency and consequences. As the study sample was comprised of sexual minority women and gender diverse young adults, future research should determine whether results generalize to other populations.